Avaliação da toxicidade pré-clínica de Foeniculum vulgare Mill - Branco, Alessandra Camillo da Silveira Castello (2009)
Foeniculum vulgare Mill. is a plant that has been known and used by mankind since antiquity because of its antimicrobial, analgesic, antiinflammatory, antispasmodic and anxiolytic properties. It is also widely used in the food and cosmetics industries. The objective of the present study was to investigate the chronic preclinical toxicity of the lyophilized crude hydroalcoholic extract (LCHAE) of the fruit of F. vulgare commercialized in sachet form in order to demonstrate the safety of its use by the population, based on Resolution 90/2004 of the Brazilian Regulatory Authorities. In this study, Wistar rats (Rattus norvegicus albinus) were treated orally with 8.5, 25.5 and 76.5 mg/kg of LCHAE for 13 weeks (n=10 per dose and sex). General signs of toxicity, lethality and food and water consumption were evaluated daily, while weight was evaluated weekly and body temperature, glucose levels and behavioral parameters using open-field and rota-rod tests were assessed every two weeks. At the end of treatment, 50% of the animals in each group were sacrificed for blood analysis and 30% were submitted to histopathology. The remaining animals then formed the satellite group that remained under observation for 21 days following treatment to evaluate the reversal and/or appearance of possible toxic effects. During the 13 weeks of treatment, no signs of toxicity were noted and none of the animals died. In the females, there was a reduction in weight and food consumption and an increase in water intake. LCHAE reduced the time both males and females spent on the rotating bar, and reduced ambulation in the females and defecation and rearing in both sexes. In both males and females, a hypoglycemic effect occurred and there was an increase in aspartate aminotransferase (AST) and alkaline phosphatase (ALP), as well as a reduction in platelet count. In the females, there was an increase in alanine transaminase (ALT), leukocytes and neutrophils and a decrease in cholesterol. In the males, a reduction in lymphocytes occurred and there was an increase in monocytes. Histopathology revealed signs of hepatotoxicity including mild portal inflammation with the presence of mononuclear exudate, hepatic lobular necrosis associated with lymphocytic/histiocytic infiltration and mild sinusoidal inflammation. In addition, there were signs of toxicity in the lungs: focal pneumonitis with alveolar septal thickening consisting of mononuclear exudate. In the satellite groups, the majority of the biochemical, hematological and histopathological alterations in the liver were found to persist, suggesting irreversibility. Further studies should be developed to confirm these findings; nevertheless, these results indicate that LCHAE is toxic particularly to the liver and lungs, in both sexes and at the three doses used.